Chemical Compositions, Antioxidant and Antifungal Activities of Melaleuca leucadendron Linn. Leaf Oils from Indonesia - Rini Pujiarti; Yoshito Ohtani; Hideaki Ichiura (Wood Research Journal, 2012)
Melaleuca leucadendron Linn. Oil, also known as Kayu Putih oil, is one of the most important non-timber forest products in Indonesia. This oil has diverse bioactivity, such as insecticidal, antifungal, antibacterial, and antiviral. This study elucidated the chemical compositions and biological activities of M. leucadendron leaf oils from Java, Indonesia in order to evaluate their potency and improve their utilization. Leaf samples of M. leucadendron in this study were collected from plantation forest in Gunung Kidul-Yogyakarta (L1), Gundih-Central Java (L2) and Sukun-East Java (L3), Indonesia in different plant ages of 5 (A1), 10 (A2) and 15 (A3) years-old. Oil samples were distillated by water-steam distillation. Identification of chemical composition of these essential oils was conducted by GC-MS analysis. The in vitro antioxidant activity was examined by 1,1- diphenyl-2-picrylhydrazyl (DPPH) method and antifungal activity was examined using a method by Wang et al. (2005) with slight modification against pathogenic fungi of Fusarium oxysporum, Thanatephorus cucumeris and Rhizopus oryzae. GC-MS investigations of M. leucadendron leaf oils showed 26 compounds have been identified. The result showed 1,8-cineole (44.76% to 60.19%) was the major compound in these oil, followed by α-terpineol (5.93% to 12.45%), D(+)-limonene (4.45% to 8.85%), and β-caryophyllene (3.78% to 7.64%), respectively. The in vitro DPPH assay showed anti-oxidative (IC50: 7.21 to 9.46 mg/ml) properties of M. leucadendron leaf oils. This essential oils also revealed inhibitory effect against F. oxysporum (IC50: 0.01 mg/ml to 0.11 mg/ml), T. cucumeris (IC50: 0.52 mg/ml to 4.20 mg/ml) and R. oryzae    (IC50:1.35 mg/ml to 7.61 mg/ml). The antifungal activity showed M. leucadendron leaf oils were effective against fungi of F. oxysporum and T. cucumeris; but it showed less antifungal activity against R. oryzae. This study indicated that the M. leucadendron leaf oils can be used as antioxidant and sustainable eco-friendly bio fungicides.